Safety and efficacy of catheter ablation for atrial fibrillation in the very elderly. (3rd October 2022) - Wahedi, R; Willems, S; Jularic, M; Hartmann, J; Schaeffer, B; Akbulak-Stegli, Ö; Eickholt, C; Anwar, O; Maurer, T; Hedenus, K; Gunawardene, M
Abstract: Background: The incidence and prevalence of atrial fibrillation (AF) increases with age. With an ageing general population, a 2.3-fold rise in AF prevalence is expected. Catheter ablation has emerged as an effective treatment option for rhythm control therapy. However, very elderly patients (≥80 years old) have been excluded in landmark clinical trials. Current data regarding the safety and efficacy of catheter ablation in the very elderly is therefore sparse. Purpose: Due to the growing demand to manage AF in an increasingly ageing population, we investigated the safety and efficacy of catheter ablation in this particular patient population. Methods: Patients with symptomatic paroxysmal, persistent and long-standing persistent AF aged ≥80 years undergoing catheter ablation, including first and re-ablation procedures in a single centre, were analysed retrospectively. Catheter ablation involved pulmonary vein isolation (PVI) using radiofrequency, cryoballoon and pulsed field ablation as energy sources. Re-ablation procedures included re-PVI and consecutive atrial tachycardia ablation including atrial lines and/or ablation of complex fractionated atrial electrograms (CFAE) in persistent AF. Endpoints included acute procedural success (complete isolation of pulmonary veins and/or non-inducibility in the case of atrial tachycardia), major complications and early arrhythmia-recurrence. Results: A total of eighty-eight patients (mean age 83.1±1.9 years, mean CHA2DS2-VASc-Score 4.4±1, mean left ventricular ejection fraction 56.7±7%, direct oral anticoagulation 92.1%, vitamin-K antagonists 7.9%) were included from January 2021 to October 2021. Fifty cases (56.8%) involved PVI as an index procedure (radiofrequency 58%, n=29/50, cryoballoon 36%, n=18/50, pulsed field ablation 6%, n=3/50). Thirty-eight procedures (43.2%) involved re-ablation procedures (Re-PVI 60.5%, n=23/38, linear lesions 65.8%, n=25/38, atrial tachycardia ablation 26.3%, n=10/38 and ablation of CFAE 15.8%, n=6/38). Acute procedural success was achieved in 87/88 patients (98.9%). Major complications included stroke (n=1/88, 1.1%), pericardial tamponade (n=1/88, 1.1%) and bradycardia with subsequent pacemaker implantation (n=3/88, 3.4%). No further major complications were documented. In 13/88 patients (14.8%) early arrhythmia-recurrence occurred (38.5%, n=5/13 after the index procedure and 61.5%, n=8/13 after re-ablation) during the 90-day blanking period. Conclusions: Catheter ablation for atrial fibrillation in the very elderly shows favourable acute success and low complication rates. Long term success of catheter ablation and superiority to rate control in this patient population is unknown and requires investigation in the future. Funding Acknowledgement: Type of funding sources: None.